Ulnar length – A Tool for Stature Estimation (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stature is a important factor in identification of an unidentified dead body or any mutilated part of suchbody. In present study we made an attempt to estimate the stature from percutaneous length of ulna. Studyconsists of 94 adult males and 96 adult females between the age group of 18- 24 years, born and broughtup in Maharashtra. The length of the of the right and left ulna was measured with a venier calliper from theapex of the olecranon to the styloid process and the height of the individual was measured with a calibratedstanding meter rule. The measurements were noted in the proforma. The data was statistically analyzed andlinear regression formulae were derived.
Keywords: Ulnar length, Stature, Linear regression.